An historical wealth assessment – measuring the Swedish national wealth for the nineteenth and twentieth centuries. Issue 2 (3rd May 2016) - Lindmark, Magnus; Andersson, Lars Fredrik
ABSTRACT: This article provides historical account of wealth accumulation and composition in Sweden during the nineteenth and twentieth centuries. A detailed account on capital formation during the industrialisation process shows that produced capital grew faster than natural capital from the 1850s. Natural capital was changing from a predominance of forest towards crop land as the main asset in the early twentieth century. Produced capital was largely bounded in the agriculture sector up till the second half of the nineteenth century. Heavy investments in the infrastructure sector and later in the manufacturing section changed the produced capital structure and thereby lowered transport costs and return of investment in manufacturing and services; providing incentives for accumulating the stock of produced capital and enhance consumption and living standard. The return on capital was dispersed from the outset of the period but has converged over time.